Cancer in Rwanda. - Newton, R; Ngilimana, P; Grulich, A; Beral, V; Sindikubwabo, B; Nganyira, A; Parkin, D (1996)
Data are presented on the frequency of malignant tumours registered at the population-based cancer registry in the southern prefecture of Butare, Rwanda, from May 1991 until 2 months before the outbreak of civil war in April 1994. Beginning in 1992, subjects were also interviewed about socio-demographic and life-style factors that have been associated with cancer risk in the West. The distribution of cancer in Rwanda is similar to that in other countries in sub-Saharan Africa. The most frequent cancers are those with possible infectious aetiologies: liver cancer (12%), cervical cancer (12%) and stomach cancer (9%). In addition, cancers known to be associated with HIV infection are relatively frequent (Kaposi's sarcoma [6%] and non-Hodgkin's lymphoma [3%]). Chronic infection, including infection with HIV, high parity and multiple sexual partners are important determinants of cancer incidence in this population. Tobacco consumption is low in Rwanda and there are few tobacco-related tumours, such as lung and laryngeal cancer. Other tumours believed to be associated with aspects of Western life-style, such as colorectal and breast cancer, are also relatively infrequent.